2023
DOI: 10.1038/s41398-023-02366-w
|View full text |Cite
|
Sign up to set email alerts
|

Changes at glutamate tripartite synapses in the prefrontal cortex of a new animal model of resilience/vulnerability to acute stress

Abstract: Stress represents a main risk factor for psychiatric disorders. Whereas it is known that even a single trauma may induce psychiatric disorders in humans, the mechanisms of vulnerability to acute stressors have been little investigated. In this study, we generated a new animal model of resilience/vulnerability to acute footshock (FS) stress in rats and analyzed early functional, molecular, and morphological determinants of stress vulnerability at tripartite glutamate synapses in the prefrontal cortex (PFC). We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 92 publications
2
18
0
Order By: Relevance
“…Recently, we introduced the use of the sucrose intake test in rats exposed to acute FS as a rapid screening tool to distinguish acute stress-vulnerable from -resilient animals and to identify early determinants of a pro-adaptive or maladaptive stress response [43]. As previously shown, a single session of acute inescapable FS selectively triggers anhedonic behavior in a subpopulation of stressed rats, thus considered FS-V. We have also previously reported that the anhedonia observed in FS-V lasts more than a week and is reversible, that glutamate release is differentially activated in neurons and astrocytes, and that FS-R and FS-V differ in expression levels of astrocytic proteins that regulate glutamate homeostasis, suggesting glial involvement in promoting a pro-adaptive or maladaptive response to FS [43]. Notably, a multiomics study has shown that glial cells are the major contributors to the transcriptional bulk sequencing signal observed after acute stress [65].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we introduced the use of the sucrose intake test in rats exposed to acute FS as a rapid screening tool to distinguish acute stress-vulnerable from -resilient animals and to identify early determinants of a pro-adaptive or maladaptive stress response [43]. As previously shown, a single session of acute inescapable FS selectively triggers anhedonic behavior in a subpopulation of stressed rats, thus considered FS-V. We have also previously reported that the anhedonia observed in FS-V lasts more than a week and is reversible, that glutamate release is differentially activated in neurons and astrocytes, and that FS-R and FS-V differ in expression levels of astrocytic proteins that regulate glutamate homeostasis, suggesting glial involvement in promoting a pro-adaptive or maladaptive response to FS [43]. Notably, a multiomics study has shown that glial cells are the major contributors to the transcriptional bulk sequencing signal observed after acute stress [65].…”
Section: Discussionmentioning
confidence: 99%
“…Adult male Sprague-Dawley rats (175-200 g at the beginning of the protocol) were exposed to acute inescapable FS and deemed FS-R or FS-V as reported in Bonifacino et al [43]. After obtaining the required licenses (N 521/2015-PR and 140/2014-B-DGSAF24898), all experimental procedures were performed following the European Community Council Directive 2010/63/UE and the Italian D.L.26/2014.…”
Section: Animal Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult male Sprague-Dawley rats (175–200 g at the beginning of the protocol) were exposed to acute inescapable FS and deemed FS-R or FS-V as reported in Bonifacino et al [ 50 ]. After having obtained the licenses required (N 521/2015-PR and 140/2014-B-DGSAF24898), all experimental procedures were performed according to the European Community Council Directive 2010/63/UE and the Italian D.L.26/2014.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we used a recently validated rat model of resilience/vulnerability to acute inescapable footshock stress (FS) [ 50 ] to investigate the functional, molecular, and morphological determinants of the adaptive/maladaptive response to traumatic stress. Our experiments were performed in the rat prefrontal cortex (PFC) where we examined the density and function of astrocytes, microglia, and neurons.…”
Section: Introductionmentioning
confidence: 99%